PSYCHOTHERAPEUTIC CARE IN THE SYSTEM OF COMPREHENSIVE REHABILITATION OF PERSONS WITH LIMB AMPUTATION - L. I. Mostovaya; E. P. Krivoschekov; E. B. Elshin; V. E. Romanov; M. Y. Khoroshilov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Purpose. Study of the influence of psychotherapeutic assistance on the rehabilitation of persons who have undergone limb amputation. Materials and methods. A study of the psychological characteristics of 48 patients who underwent amputation of the lower extremity was carried out  on the basis of the departments of vascular surgery and traumatology of the Samara Seredavin Regional Clinical Hospital. The control group included 25  people (16 men, 9 women), aged 45 to 70 years. Amputations of the  extremities were performed by him in connection with the developed gangrene due to obliterating vascular diseases. The main group consisted of 23 people (14 men, 9 women) aged 35 to 60 years with a stable and prosperous social status, who received an acute sudden injury that ended in amputation of one or both lower extremities. The examination was carried out on the 3-5th day of the postoperative period, depending on the  patient's condition. For the study, the following psychodiagnostic methods  and techniques were used: 1) clinical conversation; 2) coping test by R. Lazarus, S. Folkman; 3) methodology for diagnosing the type of attitude to  the disease; 4) Hamilton Depression Scale; 5) S. Rosenzweig's test of drawing frustration. Results. The difference between the group of patients and the control group was statistically confirmed in terms of “seeking social support” (higher  in the control group), “confrontation” and “flight – avoidance” (higher in the group of patients) (p < 0.05). In the control group, depression is absent in 85% of the subjects, in 15% of patients there is a mild depressive  state (p < 0.05). According to S. Rosenzweig's method, the  predominance of extrapunitive reactions was revealed in both groups (E = 59.6 in the main group of patients and 44.1 in the control group) due to  reactions of the ego-protective type (ED = 56.2 in the main group of patients and 46.3 – in the control group). Conclusion. Patients who underwent surgery for limb amputation and who took a conscious and active part in individual and group psychotherapy by the time of discharge from the hospital showed a decrease in anxiety and  depressive manifestations, a decrease in the manifestations of outward aggression, the construction of optimistic prospects) than in patients who  categorically refuse to receive psychological help and support. The provision  of psychotherapeutic assistance to persons after amputation of limbs should begin in the first days after the operation.